Author Correction: A RAB35-p85/PI3K axis controls oscillatory apical protrusions required for efficient chemotactic migration - Salvatore Corallino (Nature Portfolio, 2018)
The originally published version of this Article contained an error in the name of the author Salvatore Corallino, which was incorrectly given as Corallino Salvatore. This has now been corrected in both the PDF and HTML versions of the Article.